4-(N-Phenyl-N′-substituted benzenesulfonyl)-6-(4-hydroxyphenyl)quinolines as inhibitors of mammalian target of rapamycin. Issue 15 (1st August 2015) - Venkateswarlu, Vunnam; Pathania, Anup Singh; Aravinda Kumar, K.A.; Mahajan, Priya; Nargotra, Amit; Vishwakarma, Ram A.; Malik, Fayaz A.; Sawant, Sanghapal D.
Graphical abstract: Abstract: A series of 4-( N -phenyl- N ′-substituted benzenesulfonyl)-6-(4-hydroxyphenyl)quinolines was designed, synthesized and evaluated for their biological potential as anticancer agents by screening the molecules against panel of five human cancer cell lines viz . HL-60, MiaPaCa-2, HCT116, PC-3 and HEP-G2. The series has shown good mTOR inhibitory activity at 0.5 μM concentration. The representative compound 7h was found to be most active with the IC50 of 613 nM against mTOR. In supportive evidence, the western blotting experiment revealed that compound 7h is more potent in inhibiting p-mTOR (S2448) activity in 2–4 h at 5 and 10 μM concentrations and was selective and specific towards mTORC1 versus mTORC2. Towards understanding the mechanistic aspects we studied cell cycle analysis, mitochondrial membrane potential loss in MiaPaca-2 cells for compound 7h . The docking study for this series was performed to understand the binding mode of the compounds and its consequent effect in biological activity, the initial interaction studies were found to be useful in design of molecules, where compound 7h has shown additional H-bond interaction with Lys2171 apart from Val2240 and also a small hydrophobic cleft was observed with Leu2185, Met2345 and Ile2356.